2018
DOI: 10.11648/j.jfa.20180601.12
|View full text |Cite
|
Sign up to set email alerts
|

Internal Corporate Governance and Financial Performance Nexus; a Case of Banks of Pakistan

Abstract: The persistence of corporate governance (CG) is to expedite operative and cautious management which can transport the enduring success of the company. The performance of any firm or bank is vibrantly enhanced by corporate governance. The key contribution of this study to governance literature is that; it demonstrates how the presence of the internal governance mechanism influence the bank performance. The study makes an attempt to measure the impact of internal governance indicators (Board Structure and Owners… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In their study, (Hutchinson & Zain, 2009) examined a sample of 60 Malaysian enterprises and concluded that there was no statistically significant relationship between the presence of an independent audit committee and firm performance. Other researchers that share similar views include (Al-Matari et al, 2012;Ghabayen, 2012;Bashir et al, 2018). Conversely, Dar et al (2011 discovered an inverse correlation between the variables.…”
Section: Literature Review and Hypotheses Development Audit Committee...mentioning
confidence: 85%
“…In their study, (Hutchinson & Zain, 2009) examined a sample of 60 Malaysian enterprises and concluded that there was no statistically significant relationship between the presence of an independent audit committee and firm performance. Other researchers that share similar views include (Al-Matari et al, 2012;Ghabayen, 2012;Bashir et al, 2018). Conversely, Dar et al (2011 discovered an inverse correlation between the variables.…”
Section: Literature Review and Hypotheses Development Audit Committee...mentioning
confidence: 85%
“…EPS is measured by dividing the net income available to shareholders by the number of shares outstanding with information taken from the company's financial statements in the study period [132].…”
Section: Independent Variablesmentioning
confidence: 99%
“…Therefore, failure of bank governance explains any similar crises that (may) occur in the future. Several studies have focused on bank corporate governance (Bashir et al, 2018;Sohail et al, 2017).…”
Section: Introductionmentioning
confidence: 99%